Aktivitas antibakteri ekstrak terstandar akar sidaguri (S.rhombifolia) terhadap E. faecalis dan Actinomyces spp. Antibacterial activity of standardized extract of sidaguri root (S.rhombifolia) against E. faecalis and Actinomyces spp. - Maria Tanumihardja; Darmayana Darmayana; Nurhayati Natsir; Indrya K. Mattulada (DiscoverSys Inc., 2013)
According to 2009 Indonesian Health Profile Data, pulp and periapical diseases were 8thof the 10 outpatients athospital. This situation tends to increase become the big of 7. Pulp and periapical diseases occur due to bacterialinfection in the pulp tissue. The bacteria are often found in the root canal, namely E. faecalis, and Actinomyces spp.Various herbs commonly used by people to treat dental diseases, i.e. root sidaguri. However, sidaguri plants have notbeen studied in the field of dentistry as an antibacterial. This study aimed to determine the effects of root sidaguriagainst E. faecalis and Actinomyces spp. Inhibition test of ethanol extract of the roots sidaguri against E. faecalis andActinomyces spp. using agar diffusion method at concentrations of 5%, 10%, 15%, and 20% based on themeasurement of inhibition zone by each concentration. The greatest inhibition against E. faecalis was performed by concentration of 20% (p<0.05), while no inhibition zone was found on Actinomyces spp. It was concluded that theethanol extract of the sidaguri roots was the most effective against E. faecalis at concentration of 20%, but not effectiveat all against Actinomyces spp.